Determining geological relationships that lead to the locations of focused and diffuse vents on the Brothers Volcano, using seafloor imaging and EM300 multibeam bathymetry - Broomfield, Thomas (My University, 2010)
The Brothers volcano in the Kermadec Arc has an active and extensive hydrothermal venting system. Using multibeam sonar survey and an underwater camera (TowCam), this study documents the geological features association with the Brothers vents. Photographs show the seafloor with its various geological formations.
Senior thesis written for Oceanography 444
Keywords: Submarine geology; South Pacific Ocean--Kermadec Arc--Brothers volcano; Hydrothermal vents--Geology--South Pacific Ocean